URGENSI KLAUSULA BAKU DALAM AKTIVITAS BISNIS - Arif Hariyanto; Ika Fitriana (Al-Hukmi : Jurnal Hukum Ekonomi Syariah dan Keluarga Islam, 2020)
The term standard clause is often used specifically in the practice ofbuying and selling that occurs between businesses and consumers.Consumers are forced to accept it even though this is a unilateralagreement in the form of transfer of responsibility by business actors toconsumers. As a result of the existence of this standard clause if there is adefect in the goods that have been purchased, the consumer cannotreturn the item back wherein in Islamic law the business / purchasetransaction is determined by the validity of a contract that is carried outand discussed in the division of khiyar rights. In addition, this standardclause is also regulated in Law No. 8 of 1999 concerning ConsumerProtection (UUPK).Thus, the focus of this research objective is to find out the application ofstandard clauses in business practices and to describe the approach ofIslamic law and La w no. 8 of 1999 concerning consumer protectionagainst standard clauses in business practices or buying and selling.In the approach of Islamic law the application of this standard clausemust be carried out in an interadin manner. While according to Law no. 8of 1999 concerning Consumer Protection (UUPK) the application of thisstandard clause continues to provide protection for consumers infulfilling the rights of consumers to be served properly and notdiscriminatory as well as the right to get compensation in the form ofreplacement of similar goods if there is a disability.